Comparative Analysis of Russian and Foreign Experience in Managing Enterprises' Intellectual Property - BYKOVA, Olga Nicolaevna; GARNOV, Andrey Petrovich; MORKOVKIN, Dmitry Evgenievich; STROEV, Pavel Victorovich; RUDENKO, Lyudmila Gennadievna; ZONOVA, Alevtina V.; LIVANOVА, Rimma V.; ISAICHYKOVA, Natalia Ivanovna (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019DO - 10.14505//jarle.v10.4(42).06, 2019)
The objective of the research is to study Russian and foreign experience in managing intellectual property in the authorized capital, as well as to develop ways to improve the approaches to the capitalization of an enterprise’s intellectual property. Methods : The role and quantity of the results of intellectual activity as a company's competitive advantage are increasing in the modern world. Intellectual capital is the main resource for a company. In Russian practice, there is a lack of awareness about the proper maintenance of accounting and effective management of intellectual property. Therefore, the authors, first, conducted a comparative analysis of Russian and foreign practices and identified the ways and areas for improvement. Second, the authors considered the specifics of creating an intellectual property management system at an enterprise. Third, they developed the methods for adapting foreign experience to the Russian economy. Fourth, the prospects for accounting the intellectual property items in the authorized capital of enterprises were considered. Recommendations were made for accounting and tax accounting. In cases when intangible assets are included in the turnover, an acceptable cost should be guaranteed, and the maximum value should be set for the commercialization of intellectual property. Second, special attention should be paid to the development of recommendations aimed at improving the results of the use of intellectual property and intellectual rights, which will lead to an increase in productivity and speed of work. The study results will allow improving the financial condition of a company through the capitalization of an organization’s intellectual property from the perspective of foreign experience. The proposed methods will help organizations to improve their financial condition through the capitalization of their intellectual property items.